1996
DOI: 10.1073/pnas.93.5.1897
|View full text |Cite
|
Sign up to set email alerts
|

Midcycle administration of a progesterone synthesis inhibitor prevents ovulation in primates.

Abstract: Progesterone receptors appear in granulosa cells of preovulatory follicles after the midcycle gonadotropin surge, suggesting important local actions of progesterone during ovulation in primates. Steroid reduction and replacement during the gonadotropin surge in macaques was used to evaluate the role of progesterone in the ovulatory process. Animals received gonadotropins to induce development of multiple preovulatory follicles, followed by human chorionic gonadotropin (hCG) administration (day 0) to promote oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 40 publications
6
69
0
Order By: Relevance
“…First, high levels of estradiol are absolutely essential (Brom and Schwartz, 1968;Ferin et al, 1969;Labhsetwar, 1970). Second, estradiol induced progesterone receptors (PR) in the hypothalamus are needed (Chappell et al, 2000;DePaolo, 1988;Hibbert et al, 1996;Mahesh and Brann, 1992;SanchezCriado et al, 1994;Snyder et al, 1984). Third, preovulatory progesterone is also essential for the gonadotropin surge (DePaolo, 1988;Hibbert et al, 1996;Mahesh et al, 1992;Micevych et al, 2003;Remohi et al, 1988).…”
Section: Model Of Estrogen Positive Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…First, high levels of estradiol are absolutely essential (Brom and Schwartz, 1968;Ferin et al, 1969;Labhsetwar, 1970). Second, estradiol induced progesterone receptors (PR) in the hypothalamus are needed (Chappell et al, 2000;DePaolo, 1988;Hibbert et al, 1996;Mahesh and Brann, 1992;SanchezCriado et al, 1994;Snyder et al, 1984). Third, preovulatory progesterone is also essential for the gonadotropin surge (DePaolo, 1988;Hibbert et al, 1996;Mahesh et al, 1992;Micevych et al, 2003;Remohi et al, 1988).…”
Section: Model Of Estrogen Positive Feedbackmentioning
confidence: 99%
“…Second, estradiol induced progesterone receptors (PR) in the hypothalamus are needed (Chappell et al, 2000;DePaolo, 1988;Hibbert et al, 1996;Mahesh and Brann, 1992;SanchezCriado et al, 1994;Snyder et al, 1984). Third, preovulatory progesterone is also essential for the gonadotropin surge (DePaolo, 1988;Hibbert et al, 1996;Mahesh et al, 1992;Micevych et al, 2003;Remohi et al, 1988). Most models of the LH surge use both estradiol and progesterone priming because ovariectomized rats treated with only estradiol show a physiological, but blunted LH surge, but treatment with progesterone increases the magnitude and duration of the surge (DePaolo and Barraclough, 1979).…”
Section: Model Of Estrogen Positive Feedbackmentioning
confidence: 99%
“…This process consists of a complex series of events tightly coordinated by a network of paracrine and endocrine signals, most notably in mammals by steroid progesterone signaling, in mature follicles (3)(4)(5). Pharmacological inhibition of progesterone synthesis or genetic disruption of the progesterone receptor results in an ovulation failure due to a lack of follicle wall proteolysis or follicle rupture (6,7). The signaling mechanism by which progesterone regulates a spatiotemporal proteolysis leading to a successful follicle rupture is largely unknown.…”
mentioning
confidence: 99%
“…In rodents, ovulation is preceded by a small increase in progesterone as well as an increase in oestradiol, prolactin and LH. The preovulatory rise in progesterone has been shown to be mandatory for ovulation (Hibbert et al 1996;Robker et al 2000) and its absence in LRH-1-KD mice could largely explain the observed infertility phenotype. The progesterone receptorknockout (PRKO) mice, in which both progesterone receptors have been inactivated, are completely infertile (Robker et al 2000;Conneely et al 2003), like LRH-1-KD mice.…”
Section: Discussionmentioning
confidence: 99%